A PRELIMINARY STUDY ON BHADALWADI LAKE ALGAL BIODIVERSITY - BIBHISHAN MAHADIK,; PANCHSHILA KABNOORKAR, (The Bioscan, 2025)
Bhadalwadi Lake in Indapur Tehsil, Pune district, Maharashtra, has been chosen to be the site of a study on the algal diversity in freshwater habitat. During the 24 months from June 2022 to May 2024, the investigation was conducted. In present investigation, Algae belonging to 29 genera were found to have 36 species. 36 species represent the four classes of algae. Chlorophyceae and Cyanophycean members were found dominant followed by Bacillariophyceae. One member of the Euglenophyceae, Euglena proxima Dangeard, is the most abundant during the summer. Chlorophyceae members mostly found in rainy and winter season whereas Cyanophycean and Bacillariophyceae found in summer season mainly. There were many different types of algae present in Bhadalwadi Lake, both in terms of number and quality. The species of Oedogonium, Hydrodictyon, Ankistrodesmus, Spirogyra, Zygnema, Navicula Nitzschia, Chroococcus, Merismopedia, Spirulina, Phormidium, Nostoc and Scytonema were dominant in Bhadalwadi Lake. Stigeoclonium, Trebauxia, Characium, Pediastrum, Ankistrodesmus, Amphora, Gyrosigma, Arthrospora, Lyngbya, Plectonema present not as much of dominant species. Spirulina shows maximum species diversity i.e. 8.33%, followed by Oedogonium, Navicula, Chroococcus & Lyngbya 5.55%. The preliminary investigation shows Bhadalwadi Lake is rich with the members of Chlorophyceae and Cyanophyceae.